Analisis Pengaruh Teknologi Blockchain terhadap Transparansi dan Keamanan Laporan Keuangan - Ludmilla, Rafika; Abdillah, Nur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the impact of blockchain technology on the transparency and security of financial reports. Involving surveys and documentation studies on companies that have implemented blockchain technology, this study found that the implementation of blockchain significantly improves the transparency and security of financial reports. The results of the analysis show that blockchain provides a clear audit trail, reduces the possibility of data manipulation, and improves data protection. In addition, this study also identified a decrease in fraud incidents after blockchain implementation. However, challenges such as regulatory barriers, limited human resources, and high initial costs were also identified. The recommendations of this study include investment in education and training on blockchain and collaboration with regulators to develop a legal framework that supports the use of this technology. Thus, this study provides useful insights for academics, accounting practitioners, and policymakers in understanding the impact of blockchain technology on modern financial reporting practices. The results of this study demonstrate the great potential of blockchain in improving integrity and trust among stakeholders, but also highlight the importance of careful planning and external support for the successful implementation of this technology.